PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA PEMBELAJARAN TEKS NARASI SISWA KELAS VII SMP PAHLAWAN NASIONAL - Imtisalun Auliyah; Qurratu Ainil Hilma; Ika Febriana (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to apply project-based learning model on narrative text learning in class VII of SMP Pahlawan Nasional.. The approach used is a case study with qualitative research type. Data were collected from observation which is a type of qualitative data that is aligned to the application of project-based learning model on narrative text learning in class VII of SMP Pahlawan Nasional. The data sources used are Indonesian language teachers and seventh grade students of SMP Pahlawan Nasional. Data collection techniques use observation, interviews, tests, and documentation. The results of the study explained that the application of the project-based learning model got very good, good, and quite good results from six groups that made group writing results through data observed in the field about the beauty of their school.